Selection of Conservation Practices in Different Vineyards Impacts Soil, Vines and Grapes Quality Attributes - Chrysargyris, Antonios; Antoniou, Demetris; Boyias, Timos; Tzortzakis, Nikos G. (My University, 2026)
Cyprus has an extensive record in grape production and winemaking. Grapevine is essential for the economic and environmental sustainability of the agricultural sector, as it is in other Mediterranean regions. Intensive agriculture can overuse and exhaust natural resources, including soil and water. The current study evaluated how conservation strategies, including no tillage and semi-tillage (as a variation of strip tillage), affected grapevine growth and grape quality when compared to conventional tillage application. Two cultivars were used: Chardonnay and Maratheftiko (indigenous). Soil pH decreased, and EC increased after tillage applications, in both vineyards. Tillage lowered soil N levels through mineralization, but the vineyard with Maratheftiko cultivar had higher soil N and K levels than the vineyard with Chardonnay cultivar. No tillage reduced yield in Chardonnay; however, semi-tillage enhanced yield in Maratheftiko. There were no major changes in plant physiology, even though Maratheftiko had less variation in stomatal conductance values under the various tillage practices than Chardonnay. Tillage enhanced N and K content in Chardonnay vines during flowering, and increased N in Maratheftiko. Total phenols and antioxidant status of leaves varied, with tillage stimulating them, especially at the harvest stage. Furthermore, tillage raised grape juice total soluble solids, pH, and total phenols in both cultivars, while anthocyanins and tannins content were increased in Maratheftiko under no tillage. The results of this study may aid in the development of cultivation strategies to enable viticulture to address various environmental challenges due to climate change.
Keywords: cultivation management; grapes quality; indigenous cultivars; Semi-tillage